PENGAPLIKASIAN TEORI IMOGENE M. KING PADA KASUS KEPERAWATAN - Hesti Rahayu; Irna Nursanti (Nusantara Hasana Journal, 2024)
There are many nursing theories about the nurse-patient relationship, one of the most important is Imogene King's Theory of Goal Attaintment. The theory of relationship-based nursing is Imogene King's Theory of Goal Attaintment. Imogene King's Theory of Goal Attaintment is based on shared perceptions between nurses and patients and facilitates patient- and family-centered care. Imogene M. King put forward her theory that humans have three parts in their lives, namely the interaction of personal, interpersonal and social systems which form individual relationships with other individuals to maintain positive adaptation to their environment. The sub-mains of the interpersonal system include communication, interaction, where this process involves reciprocal relationships between one individual and another individual so that a transaction is formed. In the case of patients who need to install a pace maker to achieve a transaction, the same perception is needed between the nurse and the client. This case is suitable for the application of Imogene King's Theory of Goal Attainment in implementing nursing care.